Sovereign risk in a structural approach: Evaluating sovereign ability-to-pay and probability of default - Alexander Karmann; Dominik Maltritz (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
We quantify the probability that a sovereign defaults on repayment obligations in foreign currency. Adopting the structural approach as first introduced by Merton, we consider the sovereigns ability-to-pay, characterised by the sum of discounted future payment surpluses, as the underlying process. Its implicit volatility is inferred from market spreads. We demonstrate for the case of Latin America and Russia that our approach indicates default events well in advance of agencies and markets.
Keywords: F34; 330; Sovereign Risk; Probability of Default; Länderrisiko; Internationale Anleihe; US-Dollar; Kreditrisiko; Risikoprämie; Optionspreistheorie; Theorie; Argentinien; Ecuador; Russland